Reinterpretation of Friedmann-Robertson-Walker Universe with Variable Gravitational and Cosmological Term in Bouncing Cosmology - Meitei, Asem Jotin; Singh, Kangujam Priyokumar; Sabanam, Syed; Chanu, S. Kiranmala (East European Journal of Physics, 2024)
This paper is devoted to investigate five dimensional homogeneous and isotropic FRW model with varying gravitational and cosmological constant with cosmic time. Exact solution of the Einstein field equations are obtained by using the equation of state p = (γ −1)ρ (gamma law), where γ which is an adiabatic parameter varies continuously as the universe expands. We obtained the solutions for different values of curvature K = 0, 1,−1 by using a(t) = R0(1 + α2t2)n, where α, n and R0 are positive constants. Behaviour of the cosmological parameters are presented for different cases of the models. Physical interpretation of the derived model are presented in details. Interestingly the proposed model justified the current cosmological observations with dark energy.